Bullying Analysis in SDN Pandean Lamper 02 Kota Semarang - Anggun Dwi Setya Putri; Muhammad Arief Budiman (Universitas Sebelas Maret, 2019)
The most common causes of bullying at school come from peers or classmates and seniors. Bullying is one of the many phenomena that occur in this millennial era. Many school children are victims and also the main perpetrators of bullying cases. Therefore, the purpose of this research is to analyze bullying at SDN Pandean Lamper 02 Semarang City. This study uses descriptive qualitative methods, with data collection techniques using interviews, observation, and documentation. The research subjects were students who were perpetrators or victims of bullying, principals, and teachers. Based on research, the results obtained that bullying behavior occurs in the form of physical bullying and verbal bullying. Physical bullying involves hitting, pushing, forcing, damaging, pinching, kicking, nudging, pulling clothes and pulling hairs. Verbal bullying consists of yelling, cheering, talking dirty, mocking and calling with certain nicknames.